(untitled) - Pacult, F. Paul (New Jersey, 2005)
A Double Scotch tells the intertwined success stories of Chivas Regal and The Glenlivet—two Scotch whisky brands recognized the world-over for their unparalleled quality. Founded by Scottish grocers from Aberdeen, Chivas Regal stands as the world’s most popular prestige blended Scotch. First distilled by a pistol-packing Highlander, The Glenlivet is today the top-selling single-malt Scotch in America. F. Paul Pacult explores these two iconic spirits and tells the remarkable story of the two families who endured numerous hardships to build their brands. A business book that goes down easy, A Double Scotch tells the story of the world’s favorite whiskies, and the story of the nation and families that made them so.
Keywords: Whiskey industry,Ngành công nghiệp rượu; History,Lịch sử; Scotland,Scot-land